Comparing the disinfecting efficacies of Micro 10, Deconex, Alprocid and Microzid af on the microorganisms on radiographic equipments - Zahed Mohammadi; Jamshid Ayatollahi; Fatemeh Ezzoddini Ardakani; Fatemeh Ayatollahi; Behnaz Behniafar (Tabriz University of Medical Sciences, 2008)
Background and aims. The exposure and processing of dental radiographs are not routinely associated with the spatter of blood or saliva; however, infection control is still an issue resulting from contaminated equipment, supplies, film packets or cassettes. This study aimed at comparing the efficacy of four commercially available disinfectants on microorganisms present on the equipment of radiology department.
Materials and methods. Samples from twelve sites of the radiology department were collected using a sterile swab smeared with normal saline, which was then dipped in a test tube. Experimental surfaces were then disinfected by the spray-wipe-spray method using one of Micro 10, Deconex, Alprocid or Microzid AF disinfectants, followed by resampling. The samples were subsequently cultured on blood agar and EMB plates and the colonies were counted. Isolates were identified by biochemical tests. For statistical analysis, Wilcoxon signed ranks test, Kruskal-Wallis, Chi-square and Fisher exact tests were used.
Results. Staphylococcus aureus and coagulase-negative staphylococci had the highest and Lactobacillus spp. had the lowest prevalence before disinfection. There were significant differences between the cfu/mL of bacteria before and after disinfection with any of the four disinfectant solutions. There was a significant difference between efficacy of Deconex and Alprocid (P = 0.014), Deconex and Microzid AF (P = 0.001), and Deconex and Micro 10 (P = 0.001).
Conclusion. According to the results, Deconex has the highest disinfectant efficacy compared to other solutions.